How Inflation, Interest Rates, and Turnover Ratios Affect Stock Prices in the Pharmaceutical Sector - Rahayu Wulan Sari (one million dreams corporation, 2025)
This study aims to analyze the influence of macroeconomic variables (inflation and the BI Rate) and company financial performance variables (working capital turnover and inventory turnover) on the stock prices of pharmaceutical companies on the Indonesia Stock Exchange (IDX). The study used secondary data from nine pharmaceutical companies for the period 2017-2020 (a total of 36 observations). Data analysis was performed using multiple linear regression (panel data) using SPSS 25, preceded by classical assumption tests (normality, multicollinearity, heteroscedasticity, autocorrelation). Hypothesis testing used the F test (simultaneous) and t test (partial). The results showed that all four variables simultaneously had a significant effect on stock prices. Partially, only inflation (negative and significant effect) and working capital turnover (positive and significant effect) were proven to affect stock prices. Interest rates and inventory turnover did not have a significant effect partially. The coefficient of determination (R²) of 0.416 indicates that the independent variables explain 41.6% of the variation in stock prices. Pharmaceutical company management needs to optimize working capital turnover efficiency and anticipate the impact of inflation. Investors can consider these two variables in fundamental analysis. Further research is recommended to add other variables and extend the study period.